Energy storage systems to exploit regenerative braking in DC railway systems: Different approaches to improve efficiency of modern high-speed trains. (April 2018) - Ceraolo, M.; Lutzemberger, G.; Meli, E.; Pugi, L.; Rindi, A.; Pancari, G.
Highlights: One important bonus of railways comes from braking energy recovery. Braking energy of trains can be recovered in storage systems. High power lithium batteries and supercapacitors have been considered. Storage systems can be installed on-board or along the supply network. A simulation tool has been realised to achieve a cost/benefit analysis. Abstract: The growing attention to environmental sustainability of transport systems made necessary to investigate the possibility of energy optimization even in sectors typically characterised by an already high level of sustainability, as in particular the railway system. One of the most promising opportunity is the optimization of the braking energy recovery, which has been already considered in tramway systems, while it is traditionally overlooked for high-speed railway systems. In this research work, the authors have developed two simulation models able to reproduce the behavior of high-speed trains when entering in a railway node, and to analyze the impact of regenerative braking in DC railway systems, including usage of energy storage systems. These models, developed respectively in the Matlab-Simscape environment and in the open source Modelica language, have been experimentally validated considering an Italian high-speed train. After validation, the authors have performed a feasibility analysis considering the use of stationary and on-board storage systems, also by taking into account capital costs of the investment and annual energy saving, to evaluate cost-effectiveness of the different solutions. The analysis has shown the possibility to improve the efficiency of high-speed railway systems, by improving braking energy recovery through the installation of such storage systems.